The Path to Success: The Challenges and Coping Mechanisms in Managing Business Operations among Multi-Business Owners in the City of Koronadal - Larase, Prescious Arshel C.; Tindog, Kristine Milhea D.; Calunsag, Kherwin Claire M.; Rendaje, Zizi Ijna S.; Retuyan, Rovie Ann C.; Bermejo, Fionna Morgani; Yongque, Adylle Modge G.; Enate, Benz Joash T.; Gaygay Jr. , Carlos Friales (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Multi-business owners face various experiences in managing their businesses. These experiences can cause both positive and negative effects to a multi-business owner’s physical, mental and emotional aspects. This study aimed to investigate the experiences of multi-business owners in Koronadal City in managing multiple businesses. This research employed a descriptive qualitative approach with semi-structured interviews with five (5) participants who were multi-business owners. These personas have begun from small businesses to well-established ones, they run three (3) or more businesses, and have been in the business industry for at least three (3) years. Braun and Clarke’s (2006) thematic analysis were used to identify key themes from the interview data. The study addressed the experiences of multi-business owners in managing business operations, employees and how they cope with the challenges faced by managing multiple businesses. Analysis revealed that maintaining operations is both hard and rewarding for business owners, showing the tension between competitive demands and personal satisfaction from their work. Marketing strategies, inventory management, and tenant selection all emerge as critical to business success. Employee management is also considered as an essential theme which include setting regulations, conducting meetings, training sessions, performance-based benefits, and virtual monitoring. Monitoring corporate performance, employee disloyalty, and neurodiversity are significant challenges, however coping techniques such as one-on-one communication, problem solving, flexibility, and disciplinary actions can assist alleviate these concerns.